2015
DOI: 10.1002/admi.201500349
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Creation of Polar Translational Boundaries by Interface Engineering in Antiferroelectric PbZrO3 Thin Films

Abstract: the paraelectric to AFE phase transition, cell quadrupling in PbZrO 3 results in the appearance of TBs. These boundaries are characterized by translation vectors R = [ a / n 1 , b / n 2 , c / n 3 ], 1/ n i ( i = 1, 2, 3), which are fractions of the unit-cell translation vectors. In this work, we report on the relation between formation of polar TBs and the interfacial strain in the system of PbZrO 3 thin fi lms grown on SrTiO 3 substrates. In combination with geometric phase analysis (GPA), [ 28 ] high-angle a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 34 publications
3
19
0
1
Order By: Relevance
“…Specifically, it is found that tails of the 2D polarization vectors, composed of the fitted sinusoidal profiles, can be nicely approximated by a curtate cycloid, which has a periodicity of 4 b O along the y direction (Figure c; Figure S5, Supporting Information). When structural defects appear, e.g., the translational boundaries, the commensurate relation of polarization with lattice will be broken in periodicity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, it is found that tails of the 2D polarization vectors, composed of the fitted sinusoidal profiles, can be nicely approximated by a curtate cycloid, which has a periodicity of 4 b O along the y direction (Figure c; Figure S5, Supporting Information). When structural defects appear, e.g., the translational boundaries, the commensurate relation of polarization with lattice will be broken in periodicity.…”
mentioning
confidence: 99%
“…Information). When structural defects appear, e.g., the translational boundaries, [35,36] the commensurate relation of polarization with lattice will be broken in periodicity.…”
mentioning
confidence: 99%
“…Also, compositional and mechanical tuning seem to favor the formation of certain types of antiphase boundaries. 213…”
Section: Antiphase Boundariesmentioning
confidence: 99%
“…It should be noted that antiphase boundaries with different translational vectors exhibit different polar states, 212 Figure 27B just illustrates one of the simplest cases. Also, compositional and mechanical tuning seem to favor the formation of certain types of antiphase boundaries 213 …”
Section: Hierarchical Domain Structures and Switching In Antiferroelectric Materialsmentioning
confidence: 99%
“…[ 23–25 ] As a factor of reducing the U e , the inescapable P r , irrelevant to antiparallel cation shifts with either complete or partial offset, motivates us to find out its relationship with the ubiquitous structural defects, for example, point and planar defects. [ 26–28 ]…”
Section: Introductionmentioning
confidence: 99%